The influence of pair duration on reproductive success in the monogamous ‘Alalā (Hawaiian crow, Corvus hawaiiensis) - Barrett, Lisa P.; Flanagan, Alison M.; Masuda, Bryce; Swaisgood, Ronald R. (Frontiers in Conservation Science, 2024)
Conservation breeding program practitioners select potential mates in an attempt to maximize pair compatibility and maintain genetic diversity. Therefore, pair duration, or the number of breeding seasons that individuals retain the same mate, is practitioner-determined in these settings. There is a critical need to evaluate whether pair duration influences reproductive success in ex situ assurance populations, particularly for socially monogamous species. The 'Alalā (Hawaiian crow, Corvus hawaiiensis) is a monogamous forest bird that is currently extinct in the wild. Today, 'Alalā exist only in human care for intensive conservation breeding. We analyzed breeding program data from 2018-2021 to determine the effects of 'Alalā pair duration and age on reproduction (nest building, egg laying, hatching, and fledging). We found that pair duration does not influence reproductive outcomes, and thus practitioners can be more proactive when re-pairing birds. Female and male age, on the other hand, influenced the probability of nest building, clutch production, and overall reproductive success. Nest building and clutch production probabilities were high (near 1) and stable as females aged from 2 to 12 years old, declining sharply thereafter. In males, overall reproductive success (from building robust nests to rearing at least one nestling to fledge) increased with age from 2 to 9 years old, peaked and reached an asymptote with males ≳ 9 to 13 years old, and decreased in males ≳ 13 years old.Thus, integrating age into the pair selection process will increase the likelihood of achieving conservation goals. To our knowledge, we are the first to utilize empirical pair duration results to provide specific management recommendations for mate selection in an avian conservation breeding program. Our findings have critical utility for guiding 'Alalā pairing decisions, and more broadly underscore the importance of evaluating mate retention and selection protocols in other conservation breeding programs.